PEMULIAAN PADI SECARA PARTISIPATIF BERBASIS KONSEP KAWASAN PERTANIAN BERKELANJUTAN / Participatory Rice Breeding Based on The Concept of Sustainable Agriculture Region - Vina Eka Aristya; Taryono Taryono (Jurnal Penelitian dan Pengembangan Pertanian, 2021)
The Rice farming system has long been implemented by a typical top-down approach. The degree of creativity and autonomy of farmers has been determined by the continuous external inputs. The main challenge of rice breeding programs is to improve the quality of varieties to be developed in a specific environment and acceptable to the user community. The adoption of new varieties was limited because the breeding process has not taken into account the farmers' preferences. Another obstacle that often arises was that varieties are less adaptive in specific conditions. The variety's productivity depends on farmers' knowledge, facilities, and resource management. This paper explores the principles of participatory rice breeding and its application with a comprehensive approach that aims to encourage farmer empowerment in assembling superior varieties and providing seeds independently. Participatory breeding programs are offered as a solution in understanding the needs of sustainable agriculture. The farmers' involvement serves to capture preferences and selection of lines with high yield potential and were environmentally adaptive. Collaboration was carried out through testing the lines on farmers' land. Decentralization breeding also pays attention to the agroecological paradigm in the scale of the agricultural region. Implementation of agricultural region development serves to preserve sustainable agricultural resources and the environment. The farmers' active participation in the agricultural region has a positive impact on ecosystem sustainability, biodiversity, and environmental conservation for the future. Participatory rice breeding through integrated policies contributes to improving farmers' welfare and realizing environmental sustainability through agricultural region management.Key words: Rice, breeding, participatory, collaboration, varieties AbstrakSistem pertanian padi telah lama diterapkan dengan pendekatan top-down yang khas. Tingkat kreativitas dan otonomi petani ditentukan oleh input eksternal secara terus menerus. Tantangan utama program pemuliaan padi ialah meningkatkan kualitas varietas untuk dikembangkan di lingkungan khusus dan dapat diterima oleh masyarakat pengguna. Adopsi varietas baru terbatas karena proses pemuliaan belum memperhatikan preferensi petani. Kendala lain yang sering muncul yaitu varietas kurang adaptif pada lingkungan spesifik. Produktivitas varietas bergantung pada pengetahuan petani, fasilitas, dan pengelolaan sumber daya. Makalah ini menggali prinsip pemuliaan padi secara partisipatif dan penerapannya dengan pendekatan komprehensif yang bertujuan utuk mendorong pemberdayaan petani dalam perakitan varietas unggul dan penyediaan benih secara mandiri. Program pemuliaan partisipatif ditawarkan sebagai solusi dalam memahami kebutuhan pertanian berkelanjutan. Keterlibatan petani berfungsi untuk menjaring preferensi dan seleksi galur dengan potensi hasil tinggi dan adaptif lingkungan. Kolaborasi dilakukan melalui uji galur di lahan petani. Pemuliaan desentralisasi juga memperhatikan paradigma agroekologi dalam skala kawasan pertanian. Implementasi pembangunan kawasan pertanian berfungsi melestarikan sumber daya dan lingkungan pertanian berkelanjutan. Partisipasi aktif petani di kawasan pertanian berdampak positif terhadap kelestarian ekosistem, keanekaragaman hayati, dan konservasi lingkungan bagi masa depan. Pemuliaan padi partisipatif melalui kebijakan terintegrasi berkontribusi pada peningkatan kesejahteraan petani dan mewujudkan kelestarian lingkungan melalui pengelolaan kawasan pertanian.Kata kunci: Padi, pemuliaan, partisipatif, kolaborasi, varietas